Sôbre uma coleção de Copepodos, não parasíticos, da baía de Santos e suas adjacências: Est. I e II (Boletim do Instituto Oceanográfico, 1952)
This paper deals with the occurrence of Copepods in the Bay of Santos (State of São Paulo, Brazil) and its surroundings. During 1934-1945 the author collected plankton samples from that region not only to study its various components but especially to test its distribution in the contents of fish's stomachs. Thus, 1.136 samples were gathered, mostly from surface waters, since only 18.6% from intermediary and 8.8% from deep waters. According to the available literature, up to 1939, no important account had been given on the Copepoda from the coast of São Paulo and few works deal with this order from the Brazilian coast in general. Among them Van Douwe (1911; 1912), Wright (1927; 1935; 1936; 1936a; 1937), Kiefer (1935; 1936a; 1936&;) Chappuis (1936), Marsh (1933) and Schubart (1938-1942) who referred to some specimens from the north of Brazil. However, in all these works only brackish and fresh water specimens were considered. Later on, Oliveira (1945-1947) while carrying out researches on the micro crustácea from Guanabara Bay, presented interesting studies on marine species. A list is given of the commonest species collected and the author arrived to the following conclusions: a) excepting the genus Oithona, Paracalanus, Euterpina, Corycaeus and in certain months Acartia that, generally were found throughout the year, there was a great variation of species in the region investigated. b) In a general way, the author could not find that strict subdivision proposed by some authors who proved the existance of an absolute characteristical fauna on the surface, another intermediary one and still a bathipelagial one. This was due, perhaps, to the irregular catches and to the methods employed which could only be improved after 1947. c) Bright light did not cause the accumulation of organisms on the surface, excepting, obviously, the night catches; quite rich catches were made in misty days. d) Winds of high and medium speed had no great effect on the distribution of macroplankton while the rain seemed to help the concentration of Copepods on the surface, at least during the day; strong winds as well heavy rains drawn the plankton deeper down. e) The temperature influentiated the occurrence of material though slight changes had no great effect. f) As it was expected the zooplankton from the Bay of Santos presented the same characteristics as that from the open sea, though it proved to be poorer in quality and concerning some species, reacher in quantity. Some general considerations are made regarding the impure and contaminated water of a large city like Santos. While studying the research methods, the author gives slight references to the migration observed and to geographical distribution of some species.